Analysis of Mg(OH)2 deposition for magnesium air fuel cell (MAFC) by saline water - Sahriah Basri; Nurul Shahzira Hazri; Shanjeva Rao Selladurai; Azran Mohd Zainoodin; Siti Kartom Kamarudin; S.U. Zakaria; A.R. Hashim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Magnesium air fuel cell (MAFC) systems are eco-friendly fuel cells that use electrolytes of saltwater and oxygen from the air to produce power. However, MAFC cells face a critical problem, which is the deposition of side products on the surface of the Mg anode plate and the cathode electrode. Therefore, this study will focus on the analysis of factor on Mg(OH)2 deposition by identifying the optimal seawater, Mg alloy, and surface roughness and additives solution. Magnesium plates AZ31 are used as the anode, and air electrode as the cathode. This study also considers physical characteristics such as SEM, EDX and corrosion test while chemical characterization by performance test with difference electrolyte, anode, and roughness. Catechol-3,5-disulfonic acid disodium salt (tiron) as anti-deposition used to reduce the deposition of Mg(OH)2 on the anode and cathode surfaces and thus improve the performance of MAFC. From the performance study, the MAFC able to produce a power density of 27.54 mW/cm2 which is high compare to the MAFC without tiron. Therefore, with the active area by 110.25 cm2 , the MAFC generates 2.93 W. The deposition of Mg(OH)2 reduces the active area of magnesium oxidation, thus, reduce the electricity generation. With the knowledge of optimal seawater concentration and improvement of a single fuel cell system, this study is expecting to assist the fisheries and aquaculture sector as well as the coastal communities in terms of providing a better, safer, and cheaper alternative source of electricity.